Repeat treatment with icatibant for multiple hereditary angioedema attacks: FAST‐2 open‐label study. Issue 11 (21st September 2013) - Baş, M.; Greve, J.; Hoffmann, T. K.; Reshef, A.; Aberer, W.; Maurer, M.; Kivity, S.; Farkas, H.; Floccard, B.; Arcoleo, F.; Martin, L.; Sitkauskiene, B.; et al.
Abstract: Background: The For Angioedema Subcutaneous Treatment (FAST)‐2, a phase III, double‐blind, randomized, multicenter, placebo‐controlled study (ClinicalTrials.gov identifier: NCT00500656), established the efficacy and safety of single injections of icatibant, a bradykinin B2 receptor antagonist, in the treatment of hereditary angioedema (HAE) attacks. Here, we evaluate the efficacy and safety of repeated treatment with icatibant in adult patients experiencing HAE attacks during the FAST‐2 open‐label extension (OLE) phase. Methods: Patients completing the controlled phase were eligible to participate in the OLE phase and receive open‐label icatibant (30 mg subcutaneously) for the treatment of cutaneous, abdominal, and/or laryngeal HAE attack(s) severe enough to warrant treatment. Time to onset of symptom relief was calculated for each attack. Descriptive analyses (median, 95% CIs) were performed for all attacks; post hoc analyses were conducted in patients with at least five icatibant‐treated attacks throughout the FAST‐2 OLE phase. Safety was also monitored. Results: Fifty‐four patients received icatibant for 374 attacks (176 cutaneous, 168 abdominal, and 30 laryngeal). For cutaneous and/or abdominal attacks (attacks 2–5), the median times to onset of symptom relief ranged between 2.0 and 2.5 h. For all laryngeal attacks, the median times to regression (start of improvement) of symptoms ranged between 0.3 and 4.0 h. Post hoc analyses showed that the overall median time to onset of symptom relief was 2.0 h. Overall, 89.8% of attacks resolved with a single icatibant injection. No drug‐related serious adverse events were reported. Conclusions: These findings have demonstrated the efficacy and safety of repeated icatibant treatment for HAE attacks.